ANALISIS KEMAMPUAN MEMBACA PEMAHAMAN PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS IV SDN 52 SINGKAWANG - Tiara; Slamat Fitriyadi; Sri Mulyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The ability to read and comprehend is very important to help children learn things.Through correct and good reading activities, it is hoped that children will be able toabsorb the essence of the reading they read and get something from the readingactivities they do. This study is to find out: (1) To find out the ability of readingcomprehension in Indonesian subjects of grade IV students of SDN 52Singkawang (2) Factors that affect the ability to read comprehension in Indonesiansubjects of grade IV students of SDN 52 Singkawang. The research used isqualitative research. The subjects of this study are grade IV teachers and 10students from grade IV, where students will represent the characteristics of thepopulation as a whole. The results of the study show that (1) There are twocategories of students reading comprehension ability in Indonesian subjects,namely the middle and low categories. (2) There are two factors that affectstudents& reading ability, namely internal and external factors. In internal factors,things that affect students reading comprehension ability are emotional controland vocabulary. Meanwhile, external factors affect students reading ability,namely the family environment and the school environment.